PEMBUATAN TEMPAT SAMPAH HIDROLIK NON MESIN DI KELURAHAN DALUNG KECAMATAN CIPOCOK JAYA - Yuliah Yuliah; Guwendi Ilham Karanito; Raihan Zaki; Muhammad Firmasyah; Muhammad Faris; Nanang Sujiadi (Indonesian Collaboration Journal of Community Services, 2023)
The population of Dalung village is 8,261 people who are in 3 RWs. Based on survey data from RW 1, 2 and 3 conducted by the 2023 Bina Bangsa University KKM, only a few residents have trash cans and nearly 80% of the community burns waste in open spaces. Meanwhile, the bad impact of burning garbage will cause many health risks that are rarely known by the public. Burning garbage releases toxic substances into the atmosphere which affect the environment. The aim is to increase understanding about the community understanding the importance of disposing of waste properly. The method used is physical intervention, namely making a non-machine hydraulic garbage disposal from paint buckets and pipes. The results of the activities of the service team succeeded in completing 4 trash cans within 10 days even though in the manufacturing process we experienced problems, such as the assembly time which took quite a long time. Non-machine hydraulic trash bins are placed in RW 1, 2, 3 and Rainbow Park in Dalung Village